Synthesis, characterization, X-ray crystal structure and antibacterial activity of nickel, palladium and platinum complexes with Schiff base derived from N-cyclohexylhydrazinecarbothioamide and 5-(tert-butyl)-2-hydroxybenzaldehyde. (3rd June 2021) - Arafath, Md. Azharul; Adam, Farook; Hassan, Mohd. Zaheen
Abstract: A new 2-(5-( tert-butyl )-2-hydroxybenzylidene)- N -cyclohexylhydrazine-1-carbothio amide (H2 TBNCA) Schiff base ligand has been synthesized contain N, S and O coordinating sites and has been chelated to Ni(II), Pd(II) and Pt(II) metal ions. In all three coordination compounds, the metal ion is in square planar geometry Na[Ni(TBNCA)·OAc], [Pd(TBNCA)·dmso] and [Pt(TBNCA)·dmso] are mononuclear complexes. The structure of H2 TBNCA was elucidated by X-ray diffraction analysis. In the broth dilution method, Na[Ni(TBNCA)·OAc] exhibited significant antibacterial activity against Escherichia coli and Staphylococcus aureus with minimum inhibition concentration (MIC ) of 12.5 and 6.25 µg mL −1, respectively. [Pt(TBNCA)·dmso] also showed antibacterial activities against E. coli and S. aureus with MIC value of 25 µg mL −1, while [Pd(TBNCA)·dmso] showed lesser activity with MIC values in the range of 50–100 µg mL −1 . In the disk diffusion method, the complexes showed significant antibacterial properties against both E. coli and S. aureus, whereas the ligand did not show any significant activity. GRAPHICAL ABSTRACT: